Pengembangan Model Pendidikan Islam Transformatif Berbasis Kearifan Lokal - Muhamad Mundi; Nur Cholid; M. Ahsanul Husna (Ikatan Dai Indonesia, 2026)
Islamic education in the era of globalization faces significant challenges in preserving Islamic values while responding to rapid social, cultural, and technological changes. One strategic approach to addressing these challenges is the development of a transformative Islamic education model based on local wisdom that integrates religious teachings with the cultural values of society. This study aims to analyze and formulate a transformative Islamic education model grounded in local wisdom as a means of strengthening character development, cultural identity, and social awareness among learners. The research employs a qualitative approach using a library research method. Data were collected from books, scholarly journals, and relevant studies on Islamic education, transformative education, and local wisdom. The data were analyzed through content analysis to identify key concepts and construct an integrative educational model. The findings reveal that transformative Islamic education based on local wisdom can be developed through the integration of Islamic values, including tawhid (monotheism), morality, and humanity, with local cultural values such as mutual cooperation, deliberation, tolerance, and social responsibility. The proposed model encompasses philosophical foundations, curriculum development, learning processes, character formation, and community involvement in education. The implementation of this model contributes to strengthening Islamic identity, preserving local culture, enhancing critical consciousness, and fostering learners who are religious, adaptive, and committed to constructive social transformation. Therefore, transformative Islamic education based on local wisdom can serve as a strategic alternative for developing contextual and sustainable Islamic education in Indonesia.